In Vitro Biological Screening of Hartmannia rosea Extracts. (4th December 2017) - Rashid, Rehana; Kalsoom Khan, Abida; Ul Haq, Ihsan; Mir, Sadullah; Mehmood, Sadaf; Lu, Yi; Murtaza, Ghulam
Abstract : The present study is focused on the assessment of the medicinal therapeutic potential extracts of H. rosea to investigate their pharmacological implications based upon science proofs. The antioxidant activity of fraction of H. rosea, namely, n -hexane (HR-1), ethyl acetate (HR-2), chloroform (HR-3), and n -butanol (HR-4), was performed by using the DPPH radical scavenging method. The cytotoxicity and enzyme inhibition assessment were also performed. All the extracts showed significant antioxidant, antibacterial, and protein kinase inhibition but none of the extracts exhibited α -amylase inhibition activity. The chloroform extract HR-3 may block a kinase receptor from binding to ATP; the lead molecule will be isolated, which may stop cancerous cell growth and demotion of cell division. It is predicted that ethyl acetate, chloroform, and n -butanol extracts of H. rosea contain polyphenolics, flavonoids, and alkaloids that are biologically effective candidates exhibiting significant cytotoxicity, antioxidant, and antimicrobial activities. They may control oxidative damage in the body tissues and act as potential antidiabetic and anticancer agents. These studies will also be helpful for future drug designing and drug development research.